(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the current situation small liver fluke infection in humans, dogs/cats, snail and freshwater fish in Yen Bai province and Phu Yen province in 2020 Research method: Cross-sectional descriptive study conducted to determine the rate of human infection with small liver fluke by Kato-Katz testing method for 1,674 people. Snail testing using the shedding method, fish testing using the digestion method, dog and cat feces testing using the formaline ether method to evaluate the situation of liver fluke infection. Results: The prevalence of small liver fluke infection in human in Yen Bai province was 45.4% and in Phu Yen province was 8.1%. The rate of small liver fluke infection in men was higher than in women with infection rates of 40.5% and 19.0%, respectively. The Men infected with small liver fluke was higher 2.51 times than that in women. The rate of small liver fluke infection in fish in Yen Bai was 83.33%, in Phu Yen was 0%. The rate of small liver fluke infection in dogs and cats in Yen Bai was 22%, in Phu Yen was 0%. The rate of small liver fluke infection on snails in Yen Bai was 0.074%, Phu Yen was 0% Conclusion: The rate of small liver fluke infection in humans, dogs and cats, and fish in Yen Bai province were high, requiring active prevention measures such as Mass Drug Administration active, comprehensive prevention intervention in endemic areas of the province. Case treatment for patients who infected with small liver flukes in Phu Yen province.